Mechanisms involved in metformin action in the treatment of Polycystic Ovary Syndrome - Motta, Alicia Beatriz (2009)
The N, N dimethyl-biguanide : Metformin is an antidiabetic drug that increases glucose utilization in insulinsensitive tissues. As Polycystic Ovary Syndrome (PCOS) and diabetes share some altered parameters-such as abnormal glucose: insulin ratio, altered lipidic metabolism and insulin-resistance syndrome- the use of metformin has become increasingly accepted and widespread in the treatment of PCOS. Currently, metformin is used to induce ovulation and during early pregnancy in PCOS patients, however, a complete knowledge of the metformin action has not been achieved yet. This review describes beyond the classical reproductive action of metformin and explores other benefits of the drug. In addition, the present work discusses the molecular mechanisms involved further than the classical pathway that involves the AMP-activated protein kinase.